Factors influencing acceptance of halal logistics services among mosque management - Mat Ali, Mastura Norlaili; Kamarulzaman, Nitty Hirawaty; Abd. Latif, Ismail; Abd Rahman, Azmawani (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Consuming halalan toyibban foods are compulsory for Muslims. Most of the time people will take meal at home but they occasionally take it at difference places such as restaurant, stall as well as mosque. However, the preparation of food at these places may have halal problems which causing some doubtful about the foods being served to patrons. The problems might be occurred during the preparation of the raw materials, processing of the food and during the logistics services. Thus, the objective of this study was to investigate factors that influence acceptance towards halal logistics services among mosques management. Face-to-face interviews a structured questionnaire were carried out with selected respondents consisting of 15 mosque management. The result showed mosques’ management support, trust on supplier, and training were the three factors that influence mosques management acceptance towards halal logistics services.